Why Me? - Sarah Buss (Journal of Practical Ethics)
When a misfortune befalls us, it is natural for us to react: “Why me?” This is not just the question: “Why did this unfortunate event occur?” Nor are we simply wondering:  “Why do such things happen?” The self-reference implies a comparison we generally manage to keep at the back of our minds:  “Why did this happen to me, and not someone else?” Importantly, this is not an expression of idle curiosity.  It is an expression of shock, dismay, and disbelief.  I am interested in both the moral significance of this natural reaction and the moral significance of our disinclination to acknowledge it.  If, as I believe, we are often morally permitted to promote our own interests over the interests of others, if it is our disposition to do so that underlies the “Why me?” reaction, and if we are nonetheless right to think there is something shameful about reacting this way, what does this suggest about the moral significance of our morally permissible self-privileging behavior?  How close can we come to reconciling (i) our right to live lives that express very little concern for the fate of others with (ii) an ideal of human solidarity that manifests itself in our self-censuring attitude toward the “Why me?” thought and toward the very self-privileging actions whose moral permissibility we have least reason to challenge?